Field Research Methods in the Middle East - Clark, Janine A. (PS, political science & politics, 2006)
In recent years, a growing chorus of voices in the political science discipline has become concerned with the balance among alternative methodological approaches in empirical research and publications. Accordingly, these scholars have issued a call to further develop and refine rigorous methods for qualitative studies, in contrast to studies that rely on quantitative methods and formal modeling (Bennett, Barth, and Rutherford 2003; Yanow 2003; George and Bennett 2005). My own interest and reason for conducting the following survey is rooted in the observation, even frustration, that the literature on qualitative research methods largely focuses on democratic and not on authoritarian regimes or the Middle East in particular. Research in the Middle East is clearly essential and has received increased attention since the terrorist attacks of 9-11, but given how critical this work is and will continue to be in coming years, what are the challenges? Do qualitative methodological tools need to be adapted for research in the Middle East? And, if so, how?The author would like to thank Anna Szczurk for her help in designing the survey and the contributors to the symposium and Melissa Gabler for their help in the research and writing of the article. The author also is grateful to the survey respondents for the time and effort they devoted to answering the questions.